Comparison of Two Different Volumes of Epidural Normal Saline for Enhancing the Effects of Spinal Anesthesia in Adult Patients Undergoing Elective Lower Limb Surgeries: A Prospective Randomized Study - Shubhra K; Mohandeep Kaur; Sandeep Kumar; Amlendu Yadav; Rupesh Yadav (Archives of Anesthesia and Critical Care, 2023)
Background: The combined spinal-epidural (CSE) anesthesia technique gives a reliable subarachnoid block as well as the flexible epidural block. One of the modified technique of CSE is epidural volume expansion (EVE) in which normal saline or local anesthetic (LA) is instilled though epidural catheter leading to increase in level of sensory blockade. Aim of the study was to compare two different volumes of normal saline for enhancing the effects of spinal anaesthesia in adult patients undergoing elective lower limb surgeries. Methods: 90 patients were randomly divided into two group. Group A - 45 patients who were received intrathecal 2.0ml of 0.5% hyperbaric bupivacaine and epidural 10ml of 0.9% normal saline for EVE using CSE technique. Group B - 45 patients who were received intrathecal 2.0ml of 0.5% hyperbaric bupivacaine and epidural 15ml of 0.9% normal saline for EVE using CSE technique. Results: The demographic data were comparable in both groups. Significant difference was seen in total duration of sensory blockade between group A (192.11±9.80) and group B (Mean ± SD 215.33±17.57minutes) (p<0.0001). Total duration of motor blockade was longer in group B (Mean± SD: 181.91± 16.42) as compared to group A (Mean ± SD: 162.48 ± 9.35 minutes) (p<0.0001). Conclusion: We conclude that epidural volume expansion (EVE) with 15 ml epidural normal saline was associated with faster onset, higher level and early achieve maximum level of sensory blockade, longer two segment regression time, early onset and longer duration of motor blockade as compared to EVE with 10 ml epidural normal saline.